Phenotypic Trait Subdivision Provides New Sight Into the Directional Improvement of Eucommia ulmoides Oliver - Deng, Peng; Wang, Yiran; Hu, Fengcheng; Yu, Hang; Liang, Yangling; Zhang, Haolin; Wang, Ting; Zhou, Yuhao; Li, Zhouqi (Frontiers in Plant Science, 2022)
Eucommia ulmoides Oliver has been used extensively in many fields. To satisfy increasing demand, great efforts must be made to further improve its traits. However, limited information is available on these traits, a factor that restricts their improvement. To improve traits directionally, nine clones were assigned to six sites to analyze the effect of different variation sources (the genotype, site, and genotype × environment interaction) on the phenotypic trait. In addition, a mixed linear model was used to assess the contribution of variations. In general, for most traits the site effect accounted for a larger proportion of the variance, followed by the genotype and genotype × environment interaction effects. Genotype and site had a significant effect on all the studied traits indicating they could be improved by selecting preferable genotypes or cultivation areas, respectively. Interestingly, growth traits or economic traits could be improved simultaneously. Trait performance and stability were necessary when selecting genotypes. Moreover, the discriminating ability of genotypes should be considered in selecting cultivation areas. Annual mean temperature and annual sunshine duration proved to be crucial factors that affected the traits. They were correlated positively with the economic traits and leaf yield and correlated negatively with growth traits. These findings contributed to selecting a wider range of cultivation areas. Regarding the genotype × environment interaction effect, there were significant differences only in the gutta-percha content, the total number of leaves, and the chlorogenic acid content. These traits could also be improved by choosing appropriate genotypes for the local environment. The research has provided preliminary data of the main factors that affect the traits of E. ulmoides and offered solutions for trait improvement. This information could be a reference for the trait improvement of other plants.